Pelatihan Master of Ceremony Guna Meningkatkan Keterampilan Berkomunikasi dan Mengelola Acara Secara Profesional - Maghfiroh, Fachrial Lailatul; Suryani, Ni Kadek; Nuha, Moch. Farhan Ulin; Syah, Muhamad Arifudin; Musofa, Hasan (Welfare : Jurnal Pengabdian Masyarakat, 2023)
This activity aims to provide opportunities for students and lecturers to develop communication skills and become reliable and professional MCs. By involving 30 participants, the training was held on July 17, 2023, with Gendhis Widhi, an expert in the field of Master of Ceremonies and public communications, as speaker. The interactive learning methods used, such as group discussions, simulations, and hands-on exercises, succeeded in increasing the participants' understanding of the training material. The evaluation results showed a high level of satisfaction among the participants. They stated that there was an increase in communication skills and self-confidence after attending the training. The participants also appreciated the selection of experienced presenters and relevant materials. This activity succeeded in creating a generation of students and lecturers who are better prepared to face the challenges of a competitive world of work. With better communication skills, participants are ready to contribute to various events and activities on campus and in the community.